Development of Digital-Based Flashcard Media in Learning Islamic Religious Education and Ethics in Junior High Schools - Hasan, Meystika Maharani; Yusuf, Munir; Ahmad, Nur Hidayat (South Sulawesi Education Development (SSED), 2025)
This research aims to develop digital-based flashcard media for learning Islamic Religious Education and Ethics in grade VIII of SMP Negeri 3 Palopo City, especially in believing in Allah's books. This research uses the Research and Development (R&D) method with the ADDIE development model. The study subjects were 28 students in grade VIII, and the object was digital-based flashcard media. Research instruments include interviews, documentation, and questionnaires. The results of the study showed that digital-based flashcard media was declared valid based on the assessment of media experts (89.28%), material experts (93.18%), and linguists (89.29%). The practicality test showed very practical results, with a percentage of 94% of teachers and 85.52% of students. Thus, this digital-based flashcard media is declared very valid and practical for use in learning Islamic Religious Education and Ethics for grade VIII students of SMPN 3 Palopo.